International affairs (Royal Institute of International Affairs, 2009)
International Affairs is Britain's leading journal of international relations. Founded by and edited at Chatham House, the Royal Institute of International Affairs in London, it has not only developed a much valued insight into European policy debates but has also become renowned for its coverage of global policy issues.